ISLAMIC RELIGIOUS INFLUENCE ON THE CULTURE OF ERAU KUTAI KARTANEGARA (International Conference on Social and Islamic Studies, 2022)
The arrival of Islam in Kutai Kartanegara was brought by two clerics namely Datu Ribandang and Datu Ditiro with the acceptance of Islam by the King of the XVII century Crown Prince Mulia. The two Muballig brought an appeal, inviting the king's family and people to embrace Islam. The king also accepted the condition that Tuan Tunggang Parangan could enter into a magic battle. This was done to fulfill the request of the Crown King, but it was agreed that if the Crown King lost, he would think twice about the creed or convert to Islam. But if Tuan Tunggang Parangan (Datu Ditiro) lost, he was willing to serve the Kingdom. After fighting the supernatural powers, all were won by Tuan Tunggang Parangan. This means that the King of the Crown must keep his promise to pronounce the shahadatain through the guidance of Tuan Tunggang Parangan (Datu Ditiro). The progress of the times and its development, the influence of Islam has been very large by the people of Kutai Kartanegara. The aim is to obtain a clear picture of the development of the Islamic religion and erau culture in Kutai Kartanegara, as well as to obtain an overview of the influence of Islam on the culture of Erau Kutai Kartanegara. This research is qualitative in nature using ethnographic methods that seek to study cultural events within the scope of the Islamic religion, in the procession of carrying out the Erau culture in Kutai Kertanagara. This research will be conducted in a natural situation, so there are no limitations in interpreting or understanding the phenomenon being studied. The results of research on the traditional Erau ceremonial party are held every year as a ceremonial event in the Kutai community. Cultures are displayed both in coastal and inland cultures, for example sound art in the form of hadrah, Qasidah and barzanji, music in the form of tingkilan music, literary arts, tarsul poetry of the pantun type recited at weddings, and tasmiyah. Fashion art in the form of traditional clothes of Erau Takwo miskat, Chinese clothes, Javanese clothes and Bugis clothes, and dance arts in the form of Jeppen dance, masks, rudat, ganjar ganjur and even social and political institutions. Economy, trade were held and demonstrated again in order to refresh memory and knowledge of the traditional Erau ceremony.